The Influence of The Social Environment, Marketing Techniques, and The Form of TRP Sunda Siger Veild on Consumer Decisions in Wongsorejo District - Elfina Monica Sunarta Sunarta; Sri Usodoningtyas; Dewi Lutfiati; Nieke Andina Wijaya (Universitas Negeri Surabaya, 2025)
The diversity of tribes and cultures that make prospective brides have choices in determining the bridal makeup that will be used at their wedding. This study is to determine the social environment, marketing techniques, the form of Sundanese Siger veiled bridal makeup, and to determine the dominant factors in consumer decisions in choosing Sundanese Siger veiled makeup in Banyuwangi Regency. This type of research is quantitative with 81 respondents who use Sundanese Siger veiled makeup. The results of this study indicate that the social environment, marketing techniques, and the form of Sundanese Siger veiled bridal makeup influence consumer decisions in choosing Sundanese Siger veiled bridal makeup with a significant value of 0.000 smaller than 0.005. The dominant variable influencing consumer decisions is marketing techniques with a coefficient value of 0.672. The conclusion of this study shows that the decision of prospective brides in choosing Sundanese Siger veiled makeup is influenced by various factors, especially the social environment, marketing techniques, and the form of bridal makeup itself. Of the three factors, marketing techniques are the most dominant factor influencing consumer decisions. This shows the importance of marketing strategies in attracting consumer interest, especially in the Wongsorejo Banyuwangi area. Keywords: social environment, marketing techniques, Sundanese siger, consumer decision